Nghiên cứu động lực phân tử ảnh hưởng của đột biến E226Q đến tính chất của phức enzym CD38 với cADPR - Vận, Đặng Ứng (Vietnam Journal of Chemistry, 2014)
Using GROMACS software a molecular dynamics simulation of the cADPR-CD38 (A) and cADPR-E226Q mutant (B) complexes has been implemented. The calculation results shown that there are no obvious differences between thermodynamic properties of these complexes. However, the variations of the molecular structure and kinetic properties as well could explain the essential elimination of catalytic activities by Glu226’s mutation. In A the cADPR could embed deep toward the bottom of the active site pocket making salt bridge with a catalytic residue Glu146, while there is no such a saltbridge in B. The averaged hydrogen bond number between cADPR and protein in B is higher than in A and on the contrary, the self-diffusion coefficient of cADPR in B is about two times smaller than in A.